Sección 4. Consenso colombiano para el diagnóstico y tratamiento de los síndromes crónicos, saprofíticos y/o alérgicos asociados a Aspergillus spp., en pacientes adultos y pediátricos - José M. Oñate G (Asociación Colombiana de Infectología, 2022)
Despite the ubiquity of Aspergillus species, and the fact that a person may inhale hundreds of conidia daily, only a small proportion of patients develop an infectious disease. Aspergillus spp. can cause a wide spectrum of diseases, depending on the patient's underlying immune function; these range from an allergic syndrome, (which does not represent a true infection), a hypersensitivity reaction (ABPA), a chronic process (CPA) or invasive aspergillosis (IA). All diseases associated with Aspergillus spp. have the potential to be misdiagnosed because symptoms and/or clinical findings overlap with each other, or with other non-fungal conditions. Greater clinical recognition of the different pulmonary syndromes is needed to identify those patients who could benefit from an appropriate therapeutic approach. Multidisciplinary management is required, where the role of antifungal therapy is only established for symptomatic and/or progressive disease management, ta-king into account the potential for azole resistance, which adds to the complexity of treatment and, in some cases, limits therapeutic options.